OBTURATIVE BOWEL OBSTRUCTION CAUSED BY GALLSTONES - A. G. Khasanov; M. A. Nurtdinov; A. V. Ibraev (Вестник хирургии имени И.И. Грекова)
The article discussed the results of surgical treatment of obturative bowel obstruction caused by gallstones. An analysis of results was made in two groups of patients. Ultrasonic tomography and laparoscopic diagnostics were used in the main group. An application of modern methods of diagnostics allowed reducing of lethality rate.